Qualidade hospedeira e tabela de vida de fertilidade de Lysiphlebus testaceipes (Cresson, 1880) (Hymenoptera: Braconidae, Aphidiinae) - Silva, Robson José da (2007)
The parasitoid Lysiphlebus testaceipes (Cresson, 1880) is a promising biological control agent of aphids in protected cultivation and in the field, however little is known of suitability of hosts and its growing ratios. This study aimed to evaluate the quality of Brevicoryne brassicae (Linnaeus), Lipaphis erysimi (Kaltenbach), Myzus persicae (Sulzer), Schizaphis graminum (Rondani) Rhopalosiphum maidis (Fitch) and Aphis gossypii Glover as hosts to the parasitoid L. testaceipes and also to determine the fertility life table of L. testaceipes on the aphids R. maidis and A. gossypii. The experiments were carried out in climatic chambers at 25±1°C, RH 70±10% and 12h photophase. Fifteen parasitoid females were used on the suitability and the quality tests on the selected aphids. To determine the immature mortality, the development and the sex ratio of the parasitoid, 12 females and 480 nymphs (3 days old) of each aphid (R. maidis e A. gossypii) were used. To evaluate the longevity and fertility 15 females of the parasitoid were used. Nymphs of each host aphid (3 day old) were offered for each parasitoid female daily, until the female died, being the 300 nymphs (1st day); 250 nymphs (2nd day); 200 nymphs (3rd day); 150 (4th day) and 50 nymphs in the other days. The parasitoid did not oviposite in B. brassicae and L. erysimi, being the others species nutricionaly suitable to the parasitoid. L. testaceipes showed preference for aphids from tribe Aphidini and these hosts presented better quality to the parasitoid when compared to Macrosiphini ones. Interactions among size, preference and quality between the Aphidini were found. L testaceipes showed preference (parasitism rate 76.7%) on R. maidis, the bigger host (hind tibia with 0.281 mm). R. maidis provided bigger size (hind tibia with 0.49 mm) and higher emergence rate (95.6%) to the parasitoid when compared to A. gossypii (parasitism rate of 55.7%). Also the smaller host A. gossypii (0.289 mm) provided smaller size (0.45 mm) and higher mortality to the parasitoid (emergence rate 72.1%). However, the development time was shorter and the longevity was higher in A. gossypii (6.3 and 5.4 days, respectively) when compared to the host R. maidis (6.7 and 3.8 days, respectively), not been related to host size. L. testaceipes showed immature mortality rate of 5.6 % in R. maidis and 9.2 % in A. gossypii. The development time of L. testaceipes in R. maidis and A. gossypii was 10.2 e 10.1 days, and the sex ratio the 0.71 e 0.66, respectively. The female de L. testaceipes had fecundity of 498.8 eggs in R. maidis and of 327.8 eggs in A. gossypii and longevity of 3 and 2.8 days, respectively. The growth parameters of L. testaceipes in R. maidis and A. gossypii were, respectively RO= 205.38 and 164.08 females; rm= 0.449 and 0.431 females/females/day; λ= 1.57 and 1.54 females/day; T= 11.86 and 11.83 days and TD= 10.78 and 11.27 days. The aphids R. maidis, A. gossypii and S. graminum have great quality as a host to the parasitoid L. testaceipes. L. testaceipes show a high potential of growing on R. maidis and A. gossypii.